Endophytic Colonisation of Solanum lycopersicum and Phaseolus vulgaris by Fungal Endophytes Promotes Seedlings Growth and Hampers the Reproductive Traits, Development, and Survival of the Greenhouse Whitefly, Trialeurodes vaporariorum - Vongai M. Paradza (Frontiers Media S.A., 2021)
In the scope of mitigating the negative impacts of pesticide use and managing greenhouse whiteflies, Trialeurodes vaporariorum sustainably, 16 endophytic fungal isolates from five different genera (Beauveria, Trichoderma, Hypocrea, Bionectria, and Fusarium) were screened for their ability to colonise two preferred host plant species, namely, tomato (Solanum lycopersicum L.) and French bean (Phaseolus vulgaris L.), through seed inoculation. Seven and nine isolates were endophytic to P. vulgaris and S. lycopersicum, respectively, where significant differences in the endophytic colonisation rates were observed among the fungal isolates in P. vulgaris and its plant parts, with a significant interaction between the isolates and plant parts in S. lycopersicum. Hypocrea lixii F3ST1, Trichoderma asperellum M2RT4, Trichoderma atroviride F5S21, and T. harzianum KF2R41 successfully colonised all the plant parts of both hosts and therefore were selected and further evaluated for their endophytic persistence, effect on plant growth, and pathogenicity to T. vaporariorum adults and F1 progeny. The four endophytes remained in both host plants for the 5-week assessment with varied colonisation rates related to the strong interaction with the time, isolates, and plant parts in both hosts. The effect of the same endophytes on the different host growth parameters varied in P. vulgaris and S. lycopersicum, with T. asperellum M2RT4 not boosting the growth in both host plants while T. atroviride F5S21 resulted in enhanced shoot biomass in S. lycopersicum. T. atroviride F5S21 and T. harzianum KF2R41 inoculated S. lycopersicum plants and H. lixii F3ST1, T. asperellum M2RT4, and T. harzianum KF2R41 inoculated P. vulgaris plants had significantly lower oviposition, while nymph development in both hosts was significantly prolonged in all the endophytically–colonised plants. The endophytes H. lixii F3ST1 and T. asperellum M2RT4 significantly reduced the longevity/survival of the exposed T. vaporariorum adults and the progeny in both S. lycopersicum and P. vulgaris. The findings demonstrate the attributes of the various endophytes in host plant growth promotion as well as their effects on the life-history parameters of T. vaporariorum and could consequently be developed as potential endophytic fungal-based biopesticides for the sustainable management of the pest in S. lycopersicum and P. vulgaris cropping systems.